Chitosan powders and Ortho-R, a chitosan-containing finished product, are stable long term when stored in proper conditions - Anik Chevrier; Dong Wang; Elizabeth Ladd; Jean-Simon Blais; Marc Lavertu (Carbohydrate Polymer Technologies and Applications)
Chitosan has sometimes been perceived to have a poor stability, which may explain why only a few chitosan-based products are available commercially. The purpose of this study was to investigate the stability of two chitosan powders and of Ortho-R (ChitogenX Inc), a chitosan-containing finished product that is used as an adjunct to improve repair of soft tissues. The powders and Ortho-R product were subjected to accelerated (40 °C/75 % RH) and long-term (25 °C/60 % RH) stability testing. The chitosan number average molar mass (Mn), polydispersity index (PDI), degree of deacetylation (DDA) and water content did not change substantially throughout the stability testing period and remained within the established specifications. Forced degradation studies were also performed on the Ortho-R product by exposing it to light, heat, humidity, hydrochloric acid and hydrogen peroxide. Storing the Ortho-R product in an open vial under warm and humid conditions (40 °C/75 % RH) led to an increase in chitosan Mn and PDI. The Ortho-R product was sensitive to oxidation as revealed by a decrease in chitosan Mn and PDI. Chitosan powders and the Ortho-R finished product are stable in the long term when the proper container closure systems are used.